LA DIMENSIÓN HUMANISTA EN LA MISIÓN DE MARTIN GUSINDE. - MERLO, ALEJANDRO SERANI (Humanitas (07172168))
The article talks about the life and work of ethnologist and anthropologist Martin Gusinde, who dedicated himself to studying and documenting indigenous cultures in Tierra del Fuego and other parts of the world. Gusinde had a scientific and humanistic vocation, and his goal was to preserve and disseminate knowledge about these cultures before their extinction. The Gusinde Foundation, established in 2018, is dedicated to promoting the recovery and dissemination of Gusinde's work.